2014
DOI: 10.1007/s11250-014-0740-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of Histophilus somni with spontaneous abortions in dairy cattle herds from Brazil

Abstract: This study investigated the participation of infectious agents in spontaneous abortions and reproductive problems at eight dairy cattle herds from three geographical regions of Brazil. Fourteen aborted fetuses and the organ sections of one cow with history of repeated abortions were received for pathological evaluations and molecular diagnostics. PCR/RT-PCR assays targeted specific genes of abortifacient agents of cattle: bovine viral diarrhea virus (BVDV), bovine herpesvirus 1 (BoHV-1), Listeria monocytogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…Nevertheless, changes in weather conditions have been identified as one of the probable factors that might have contributed to an increase in BRD (LONERAGAN et al, 2001) and we have observed a significant increase of BRD in feedlot cattle during the dry relative to wet season (Baptista et al manuscript in preparation). However, the direct effects of climatic conditions per se as predisposing factors to the development of BRD has been questioned due to the absence of solid scientific data to support this theory (TAYLOR et al, 2010).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Nevertheless, changes in weather conditions have been identified as one of the probable factors that might have contributed to an increase in BRD (LONERAGAN et al, 2001) and we have observed a significant increase of BRD in feedlot cattle during the dry relative to wet season (Baptista et al manuscript in preparation). However, the direct effects of climatic conditions per se as predisposing factors to the development of BRD has been questioned due to the absence of solid scientific data to support this theory (TAYLOR et al, 2010).…”
Section: Discussionmentioning
confidence: 83%
“…Further, single and mixed infections of H. somni and H. somni with BRSV and other infectious agents have been identified in dairy calves from Southern Brazil with BRD, where predominant agents of BRD were BRSV (38.1%), BVDV (28.6%), BCoV (33.3%), P. multocida (42.85%), M. bovis (33.3%), and H. somni (19%) (OLIVEIRA, 2014). In addition, since H. somni has been increasingly diagnosed in BRD in beef cattle feedlots as well as in the development of fatal systemic (HEADLEY et al, 2013), neurological (HEADLEY et al, 2015a, and reproductive (HEADLEY et al, 2015b) disease in beef and dairy cattle herds from this country, strategic prophylactic and control measures are necessary to prevent the economic effects of widespread dissemination of this pathogen within the local cattle industry. Collectively, these findings confirmed the theory that H. somni is indeed a potential threat to the cattle industry of Brazil (HEADLEY et al, 2014), where immunization against this important pathogen of ruminants is almost nonexistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we have identified H. somni associated with several clinical manifestations in cattle (Headley and others 2013, Headley and others 2014b), it is likely that this pathogen might have been present in cattle herds from Brazil but probably underdiagnosed. The identification of BoHV-1 in one of these steers during this study is not surprising, since this virus is endemic in most cattle herds of Paraná State (Dias and others 2013), and might have been one of the stressors responsible for the development of the respiratory disease at this feedlot.…”
mentioning
confidence: 99%
“…However, the importance of these results lies in the consequences of histophilosis being transformed into a major pathogen of cattle in Brazil, considering that we have characterised the systemic disease (Headley and others 2013, Headley and others 2014a), reproductive manifestations (Headley and others 2014b) and TME (manuscript in preparation) associated with H. somni . Moreover, the consulting veterinarian responsible for a feedlot at which histophilosis was diagnosed in 10% (11/110) of the affected calves that had poor feed conversion ratios and died acutely (Headley and others 2013) has medicated all affected cattle with oxytetracycline and instituted routine vaccination against H. somni which has reportedly resolved the undiagnosed mortality at that holding.…”
mentioning
confidence: 99%